Practical and theoretical recommendations on drawing landscape compositions - Farhod Islamovich Sattarov (Science and Education, 2024)
This article talks about the landscape genre and its specific aspects. The laws of landscape work, the sequence of work stages are analyzed. Analysis of color relationships in landscape works by artists, and based on this, scientific and practical recommendations for new painting compositions are given.